E-Government in São Paulo: the case of the restructuring of Channel 156 in the city of Limeira - Conejo, Matheus Pantaroto; Moraes, Gustavo Hermínio Salati Marcondes de (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
The study aimed to identify the consequences of a low-cost restructuring process of an e-government initiative in the state of São Paulo. The measures adopted strengthened interaction between government and citizens and the initiative received an award for the good results achieved. A single-case study was carried out on Channel 156 of the municipal government of Limeira. Data were collected through semi-structured interviews, participation in meetings with the program’s managers and technicians, and analysis of internal documents available to researchers. The findings contribute to studies on the use of information technology by public agencies, an area as yet poorly explored. The research may help in restructuring similar initiatives in other contexts through the use of appropriate management and information technology tools, resulting in better service to citizens. Palavras chave: E-government. Information technology. Single-case study. Public management. Link: http://www.ies.ufpb.br/ojs2/index.php/ies/article/view/30850/16875